Does the rise in eating disorders lead to increasing risk of orthorexia nervosa? Correlations with gender, education, and body mass index. Issue 3 (3rd May 2016) - Sanlier, Nevin; Yassibas, Emine; Bilici, Saniye; Sahin, Gulsah; Celik, Bülent
ABSTRACT: Investigating eating disorders and orthorexia nervosa, especially in the young population, is an important step in taking protective precautions and identifying disease. This study was carried out to determine the relationship of eating disorders and orthorexia nervosa to gender, BMI, and field of study in a population of university students in Turkey. In all, 900 university students aged 17–23 years participated in this study. EAT-40 and ORTO-15, which are validated instruments for the screening of participants with anormal eating behaviors and orthorexia nervosa, respectively, were used. There was not a significant difference in EAT-40 scores according to gender and BMI classification. However, EAT-40 scores were high among the students in social science. The number of orthorectic participants among women is higher than that among men, and ORTO-15 scores were not associated with BMI classification and field of study. A significant negative correlation was found between EAT-40 and ORTO-15 scores.